THE ADVANTAGES OF THE MICRO EQUITY MODEL FOR MSME BUSINESS RESILIENCE IN YOGYAKARTA DURING PANDEMIC - Bambang Dwi Hartono; Ahmad Diponegoro, MSIE., Ph.D. Diponegoro; Indra Yuliawan, SE, MBA, QCRO Yuliawan (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
Many MSME business enterprises were severely hit during the Covid-19 pandemic. This study examined a micro equity financing model as an innovative answer to conventional loans in assisting MSME to survive during and after the pandemic. The micro equity financing model employed a profit-sharing system with flexible repayment and without collateral. A qualitative, descriptive data processing approach was employed. Interviews were conducted online with respondents of MSME that use the micro equity model in the Trust Network Finance (TNF) project in Yogyakarta. It was found more than 75% of MSMEs in Yogyakarta had experienced contractions on the marketing of their business. And more than 50% of MSME players in Yogyakarta had experienced problems in repaying loans due to the Covid-19 pandemic crisis. We suggested from the results that the micro equity model had shown to provide many benefits to MSME, especially in marketing and financial aspects, such as more accessible loan applications, flexible repayment schedules, and business assistance.